Fitrah According to The Qur'an: Personality Analysis Of Islamic Psychology Perspective - Jarman Arroisi; Jamal Jamal; Mohammad Khair Al-Fikry (IAIN Ponorogo, 2021)
The West secular-worldview has arisen many discipline of knowledge including modern psychology which contradicted with Islamic psychology. The understanding of modern psychology is based on a secularistic framework which caused the separation of the essential personality of human from the Creator. This paper aims to examine the concept of fitrah in the Qur’an. Using theory of Quasi-scientific Worldview and descriptive analysis method related with fitrah of human, this research produced several conclusions. First, fitrah in the psychology study on Islamic perspective is an important dimension in human life. Especially, Islamic psychology makes fitrah as human identity centered on tawhid. Meanwhile, the human personality in modern psychology did not cover the whole dimension because it only touches the jismiyah and nafsiyah aspects. Second, in Islamic psychology, the view of human personality not only discusses on the aspects of jismiyah and nafsiyah, but also emphasizes on the ruhaniyah aspect. Third, the difference dimension of ruhaniyah that makes the dimension of fitrah important because it has the recognizing of Allah as the essential sacred identity. This condition of fitrah in the human dimension has implicated for the happiness of human.